Advancement in tribological performance of hexagonal Bi2Te3 nanosheets by incorporation of Ag2MoO4 nanoparticles - Singh S.; Sahu M.; Prajapati S.; Kumar A.; Mitra M.D.; Kumar A.; Tiwary D.; Verma D.K. (My University, 2025)
The hydrothermal, and co-precipitation methods were used to synthesize bismuth telluride (Bi2Te3) nanosheets, and silver molybdate (Ag2MoO4) nanoparticles, respectively to improve the tribological activity of lubricating oil. Being a hexagonal 2D structure, Bi2Te3 nanosheets are considered to be tribologically active. With a purpose to have the tribological activity of high order, an attempt has been made to decorate Bi2Te3 nanosheets with Ag2MoO4 nanoparticles in the form of nanocomposite Ag2MoO4/Bi2Te3. The morphological analysis of Ag2MoO4/Bi2Te3 nanocomposites using HR-SEM, TEM, and HR-TEM, confirms a uniform distribution of nanoparticles throughout the Bi2Te3 nanosheets. The tribological efficacy of the extensively analyzed nanomaterials was assessed in base lube (paraffin oil) at an optimized concentration, 0.03 % w/v, employing a four-ball tester executing ASTM D4172 and ASTM D5183 tests. Based on the analyzed tribological data, mean wear scar diameter (MWD), coefficient of friction (COF), and seizure load, synthesized nano additives exhibited superior tribological performance compared to the base oil. The antiwear and antifriction efficiency was found in the following order- Ag2MoO4/Bi2Te3 ≫ Ag2MoO4 > Bi2Te3, and Ag2MoO4/Bi2Te3 ≫ Bi2Te3 > Ag2MoO4, respectively. The nanocomposites demonstrated significantly enhanced tribological activity attributable to the synergistic interaction between noncovalently bonded nanosheets and nanoparticles. All constituent elements, elemental composition, and metal oxides (Bi2O3, TeO2, Ag2O, MoO3, MoO2, and Fe2O3) formed in the tribofilm, have collectively contributed to the lubrication, were validated through energy-dispersive X-ray spectroscopy (EDX) and XPS techniques. The SEM and AFM investigations of the lubricated surface verified the result of antiwear and antifriction. © 2025 The Authors